John F. Wippel. The metaphysical thought of Gocifrey of Fountains. A study in late thirteenth-century philosophy, the Catholic University of America Press, Washington, 1981, 420 pp - Sacchi, Mario Enrique (1987)
Fil: Sacchi, Mario Enrique. Armada Argentina. Escuela de Guerra Naval; Argentina